ANTI-MALARIAL COMPOUND FROM THE STEM BARK OF Erythrina variegata - Tati Herlina; Unang Supratman; M. S. Soedjanaatmadja; Anas Subarnas; Supriyatna Sutardjo; Noor Rain Abdullah; Hideo Hayashi (Universitas Gadjah Mada, 2009)
During the course of our continuing search for novel anti-malarial compounds from Indonesian plants, the methanol extract of the bark of E. variegata showed significant anti-malarial activity toward Plasmodium falciparum in vitro using the lactate dehydrogenase (LDH) assay. The methanol extract of the bark of E. variegata was separated by using bioassay-guide fractionation. The ethyl acetate fraction showed the most activity, exhibiting equipotency against both strains of parasite with IC50 of 23.8 µg/mL against 3D7 and 9.3 µg/mL against K1. Furthermore, by using the anti-malarial activity to follow separation, the ethyl acetate fraction was separated by combination of column chromatography to yield an active compound. The chemical structure of active compound was determined on the basis of spectroscopic evidences and comparison with those previously reported and identified as an isoflavonoid, warangalone. The warangalone showed anti-malarial activity against both strains of parasite used with IC50 of 4.8 µg/mL against 3D7 and 3.7 µg/mL against K1.